The Role of Emoticons in the Comprehension of Emotional and Non-emotional Messages in Dyslexic Youth – A Preliminary Study - Leśniak, Ewa; Grzybowski, Szczepan J. (Frontiers in Psychology, 2021)
The study explored how well dyslexic youth deals with written messages in an environment simulating popular social network communication system. The messaging systems, present more and more in pandemic and post-pandemic online world, are rich in nonverbal aspects of communicating, namely the emoticons. The pertinent question was whether the presence of emoticons in written messages of emotional and non-emotional content changes the comprehension of the messages. 32 pupils aged 11-15 took part in the study, 16 had a school-approved diagnosis of dyslexia and were included in the experimental group. 16 controls had no diagnosed disabilities. Both groups viewed short messages of four types (each including 7 communicates): verbal-informative (without emoticons and emotional verbal content), verbal emotive (without emoticons, with emotional verbal content), emoticon-informative (including emoticon-like small pictures, but without emotional content either verbal or nonverbal), emoticon-emotive (with standard emoticons and including verbal emotional content). The participants had to answer short questions after quick presentation of each message that tested their comprehension of the content. RTs and accuracy of the answers were analyzed. Students without dyslexia had shorter response times to the questions regarding all types of messages than the dyslexic participants. The answers of the experimental group to the questions about the emoticon-informative messages were less correct. The study pointed tentatively to the beneficial role of emoticons (especially the nonstandard, i.e. of non-emotional kind) in reading short messages with understanding.